Lipid Peroxidation Inhibition Activity of Sintrong (Crassocephalum crepidioi-des) Leaf Extract in Rats Consuming Arak Jembrana - Widayanti, Ni Putu; Laksmita W, Ayu Saka; Apriyanthi, Desak Putu Risky Vidika; Arijana, I G K Nyoman (Makara Journal of Science, 2020)
The present study was conducted to determine the antioxidant activity of sintrong (Crassocephalum crepidioides) leaf extract to inhibiting lipid peroxidation by decreased malondialdehyde (MDA) level in the blood plasma of rats consuming arak Jembrana. The process of making sintrong leaf extract used 96% ethanol with maceration techniques. In vivo testing used five groups: (1) a control group, (2) treatment with arak, (3) treatment with arak followed by extract at a dose of 37.5 mg/kgBW, (4) treatment with arak followed by extract at a dose of 50 mg/kgBW, and (5) treatment with arak followed by extract at a dose of 75 mg/kgBW. As much as 1 cc/day of arak was provided for seven days. The extract treatment at a dose of 37.5 mg/kgBW decreased the MDA level from 21.24 nmol/L to 16.33 nmol/L. Based on a Tukey’s Honestly Significant Difference (HSDa) test, this treatment was not significantly different from that of the control group (normal condition).